Miodynamic and Radiographic Evaluation in Recreative Athletes with Patellofemoral Pain - Abiel Eugenio Garza-Borjón; Mirna González-González; José Fernando de la Garza-Salazar; Mario Simental-Mendía; Carlos Acosta-Olivo (Medicina)
Background and Objectives: Patellofemoral pain (PFP) is frequent in the young and active population. The effect of muscle strength in the lower extremities after aerobic activity in patients with this condition has yet to be detailed. Our objective was to determine if patients with PFP show alterations in lower extremity muscle strength measurements after performing a session of ten minutes of aerobic activity on a treadmill compared to people without patellofemoral pain. Materials and Methods: We conducted a prospective experimental study with a stratified, non-randomized, and non-blinded population sample with group matching, including an experimental group with PFP and a control group with no pain. Subjects completed self-reported functional questionnaires (IKDC, Kujala, KOOS, SF-12), underwent radiographic studies, and were evaluated by measuring the strength of hip and knee muscles and the Single-Leg Triple-Hop (SLTH) test before and after ten minutes of exercise on a treadmill. Results: Seventeen subjects diagnosed with PFP and seventeen control subjects were evaluated. Both groups were homogeneous and had no significant differences in the demographic variables. A wider sulcus angle at 30° (136.8 ± 3.8° vs. 132.5 ± 5.6°, p = 0.0140), a decrease strength post-exercise in the hip abductor (37.9 ± 7.1 N⋅m vs. 45.6 ± 7.7 N⋅m, p < 0.05) and knee extensor (36.0 ± 9.1 N⋅m vs. 47.7 ± 14.0 N⋅m, p < 0.05), and a shorter distance in the SLTH test (337.9 ± 74.9 cm vs. 438.6 ± 65.8 cm, p < 0.01) was recorded in subjects with patellofemoral pain. Conclusions: Subjects with PFP had an overall lower strength of hip and knee muscles, showing significant differences in the hip abductors and knee extensors between people with PFP and healthy matched controls after aerobic exercise.